HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN PERAWAT DALAM PELAKSANAAN IDENTIFIKASI PASIEN DI BANGSAL RAWAT INAP RS PKU MUHAMMADIYAH BANTUL - Yenita Diah Rahmaningrum (PSIK 16 UMY, 2016)
Background: Nursing error is the failure to plan action to be complete as expected or incorrect use of nursing plans to achieve goals. Adherence nurses in the identification of patient is expected to reduce the occurrence of nursing errors. Adherence person can be influenced by the level of knowledge. The purpose of this research is to know the correlation of level of knowledge with patient identifications adherence by Nurses in inpatient ward PKU Muhammadiyah Bantul Hospital. Methods:This research was descriptif analytic design with cross sectional. Sample research of 60 people with a samping method use accidental sampling. Data analysis method used the fisher exact test. Results: 93,3% nurses had high knowledge about patient identification and 71,7% nurses do not adherence to implementation patient identification. Correlation test results fisher exact test p = 0,570. Conclusion: There is no correlation between level of knowledge with patient identifications adherence by nurses in inpatient ward PKU Muhammadiyah Bantul Hospital. Suggestion for nurses more adherence t in the implementation patient identification and the hospital can increase the motivation of nurses in the implementation patient identification. Keywords: Knowledge, Adherence, patient Identification, patient safety